When are negative emissions negative emissions?. Issue 4 (1st March 2019) - Tanzer, Samantha Eleanor; Ramírez, Andrea
Abstract : In recent research, there are notable inconsistencies in what is called "negative emissions", and those inconsistences could have unintended consequences. Abstract : Negative emission technologies (NETs) have seen a recent surge of interest in both academic and popular media and have been hailed as both a saviour and false idol of global warming mitigation. Proponents hope NETs can prevent or reverse catastrophic climate change by permanently removing greenhouse gases from the atmosphere. But there is currently limited agreement on what "negative emissions" are. This paper highlights inconsistencies in negative emission accounting in recent NET literature, focusing on the influence of system boundary selection. A quantified step-by-step example provides a clear picture of the impact of system boundary choices on the estimated emissions of a NET system. Finally, this paper proposes a checklist of minimum qualifications that a NET system and its emission accounting should be able to satisfy to determine if it could result in negative emissions.